نموذج تعليم اللغة العربية للناطقين بغيرها في ضوء نظاريات علم اللغة الحديث - Rosyid Ridho; Humairo Toha (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2023)
Since language is as old as man, interest in it is also ancient. Scientists have occupied their thinking for centuries in search of the origin of the human language and what is the oldest language in the world. All languages originate from one source (the mother tongue). And the language used in Paradise, and how did the words follow from the beginning. Many questions have gone through experiences and debates that date back nearly three thousand years, and no one has reached a satisfactory answer to these vexed questions about the origin of language. Successive generations began asking the same questions without running a specific solution. This research will present what is related to language history in the West and the East. We will continue to discuss the emergence of modern linguistics, research methods in contemporary linguistics, and finally, what will be discussed. They concern theoretical and applied linguistics. This research aims to know the history of the modern language, its origins, trends in teaching the Arabic language, and the method used to prepare this proposal to become a scientific work that meets the existing standards and can be calculated. The author uses the library research methodology, which is an attempt to obtain data from the library.